A comparison of the ultrasonography images of the joints of patients with rheumatoid arthritis and the corresponding synovial histological findings. Issue 4 (3rd July 2016) - Abe, Asami; Ishikawa, Hajime; Nakazono, Kiyoshi; Murasawa, Akira; Wakaki, Kunihiko
Abstract: Objectives : The objective of this study is to investigate whether ultrasonography (US) images of joints that underwent surgery reflected the synovial histological findings or clinical indicators and to compare the results of the findings related to large joints (LJs) with those of small joints (SJs). Methods : The operations were performed on 215 joints in 177 patients with rheumatoid arthritis (RA). The 215 joints included 64 LJs and 151 SJs. The joints with the power Doppler (PD) signal grades 0 and 1 were assigned to group L, while those with grades 2 and 3 were assigned to group H. The Rooney score, Disease Activity Score-erythrocyte sedimentation rate (DAS28), serum matrix metallopeptidase 3 (MMP-3), and C-reactive protein (CRP) levels were determined. Results : The Rooney score, DAS28, MMP-3, and CRP levels of the LJs were significantly lower in group L than in group H. In group H, similar results were found in the LJs and SJs, with a significant increase in the disease activity, CRP and MMP-3 levels and the histological findings in comparison to group L. Conclusions : The PD signal grade was one of the indicators that reflected the degree of synovitis in the histological findings of the active joints of RA patients.